Safety and efficacy of stenting for symptomatic intracranial artery stenosis: a systematic reveiw and meta-analysis - Shi, Ting; Chen, ShiJian; Long, YongPei; Gu, ZhongDeng (Frontiers in Pharmacology, 2023)
Background:Stroke is currently the second-leading cause of death just behind ischaemic heart disease.Drug therapy is currently the standard of care for patients with symptomatic intracranial artery stenosis(sICAS).Stenting is an important treatment for the prevention and treatment of ischemic stroke. It has been suggested that vertebral artery stenting might reduce this risk,but operation-related complications limit the application of stenting in the diagnosis and treatment of ischemic stroke.The differences in the safety and efficacy of stenting combined with drugs and drugs alone in the treatment of sICAS are unclear. The aim of this study was to assess the impact of both treatment modalities on the prognosis of patients with sICAS through a systematic review and meta-analysis. Methods:The Chinese databases (CNKI, Wanfang, VIP, CBM, DUXIU) and English databases(Pubmed, Embase, Ovid_medline, Cochrane library, Web of science )were searched to identify all studies describing sICAS. The "Risk of Bias Assessment" tool and the "Jadad Scale" provided by the Cochrane Collaboration were used to evaluate the risk of bias and quality of the collected literature. The risk ratio (RR) and its 95% confidence interval (CI) were determined using Stata statistical software version 14.0. Results:A total of 11 studies were included, comprising a total of 1,915 patients.The combined results of the study showed no significant difference between the incidence of transient cerebral ischemia(TIA )and stroke in patients with sICAS treated with stent-combined drugs versus drugs alone. The incidence of death or stroke, cerebral haemorrhage, disabling stroke or death was significantly higher in patients receiving stent-combined drug therapy versus drug therapy alone for sICAS. Conclusion:Studies suggest that stenting combined with medication for patients with sICAS may increase the incidence of death or stroke, cerebral haemorrhage, stroke or death, but has no significant effect on the incidence of TIA and stroke. The studies report inadequate and conflicting data and therefore the safety and efficacy of stenting for sICAS should be interpreted with caution.